Estudio de la diversidad microbiana del compartimento C1 del sistema digestivo de la Llama (Lama glama) - Cerón Cucchi, María Esperanza (2014)
The Llama (Lama glama) is an herbivore with a digestive system which consists of three compartments. The first compartment (C1), which is similar to the rumen in ruminants, has a complex microbial ecosystem that includes bacteria, protozoa, archaea and fungi, and is where the fermentation of the consumed forage consumed, a fundamental process in the animal nutrition occurs. The C1 of llamas is poorly characterized, due to the difficulties involved in working with microorganisms that inhabit it. The purpose of this work was to contribute to the knowledge of the microorganisms present in the C1 of llamas from two different geographic regions (Buenos Aires and Jujuy). Parameters such as pH, ammonia and volatile fatty acids were quantified. The principal bacteria and metanogenic archaea that habit the C1 could be identified. Potential new bacterial species were detected; also, genus and species of protozoa were detected and quantified in this compartment. This is the first work that provides information on the quantification, detection and genetic diversity of anaerobic microorganisms in the C1 of Llama. This study provides an overview of the bacterial ecosystem of the C1 of the Llama and lays foundation for future studies